Neighborhood Effects of Public Housing: How the Level of Public Housing Concentration Influences Neighborhood Crime Levels - Joice, Paul (2007)
Public housing is plagued by the well known “not-in-my-backyard” (NIMBY) phenomenon. People may support the existence of public housing, but oppose it in their neighborhood. This is particularly relevant to “scattered site” public housing – which has a much lower density than “traditional” public housing – because, by its very essence, scattered site public housing will be “in more backyards”. Public protests against such programs have made it clear that people don’t care about the positive effects for the public housing tenants nearly as much as they care about perceived negative effects on their neighborhood. My goal is to determine whether these perceived negative effects are indeed real. I use cross-sectional data from Louisville, Kentucky to estimate the relationship between both traditional and scattered site public housing, and the crime rate in the surrounding neighborhood. Using data obtained from the Louisville Police Department and the Louisville Metro Housing Authority, I find that each type is well suited to its typical use. Scattered site public housing, in small quantities, will not lead to an increase in neighborhood crime, while traditional public housing will. However, the marginal increase in crime is much higher for scattered site units. In fact, the addition of one traditional public housing unit at the margin is actually associated with a decrease in crime in my sample. I conclude that there is no statistically significant relationship between scattered site housing and crime; therefore, opposition to small scale scattered site housing projects is not justified by the “there goes the neighborhood” argument. Although the following calculation is based on statistically insignificant results, it appears that scattered site housing will not increase neighborhood crime unless the unit density approaches 50 units per square mile – a level attained by only one census tract in Louisville. Below this level, scattered site housing may actually decrease crime. However, scattered site housing is not a panacea. When public housing with a scattered site form and label approaches the density of traditional public housing (greater than 50 units per square mile), it could have a more adverse impact on the community than a traditional public housing project would have. Thus, when it is necessary to provide many new units, traditional, high density public housing may be the better alternative